Work-orientated learning: The use of case studies in business education from a student’s perspective - Heuer, Sarah [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2022)
„In order to integrate practical and work-orientated teaching-learning concepts into commercial vocational education and training courses, the use of simulations is recommended, especially at fulltime vocational schools. In Germany, the use of business case studies has also been discussed and recommended for many years. Against this background, it is surprising that there are hardly any empirical findings on the use and impact of these case studies in German commercial schools. This study, therefore, addresses this research gap and focuses on the student perspective in commercial education in the German vocational education and training system. A total of 305 online-questionnaires from students at different vocational schools in the German states of North Rhine-Westphalia and Lower Saxony, from the commercial-administrative sector, were included in the evaluation. In the questionnaire, the areas of student knowledge in relation to case studies, frequency of use of the case study method, perception of the achievement of the intended didactic goals and the development of student interest in the use of the method, were determined. The findings show that only about half of the students surveyed at the commercial schools, have had experience with case studies. However, the findings also show that the use of case studies was perceived positively by the students surveyed. The students were particularly positive regarding the promotion of independence to plan their own learning process through the use of case studies. In addition, the data collected could empirically prove that a high situational interest of the students, and the perceived motivation when working with case studies, correlate positively with each other. Keywords: case study, vocational education, Germany, student perspective, didactic goal achievement, interest, practical relevance.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; S 1.3.3 Vollzeitschulische Berufsausbildung; L 2.3 Methoden; 370; Berufsschule; Wirtschaftsschule; Unterrichtsmethode; Unterrichtsgestaltung; Fallstudie; Zufriedenheit; Nordrhein-Westfalen; Niedersachsen